Regeneration of Dutch Urban Districts - the Role of Housing Associations - Hugo Priemus (European Regional Science Association (ERSA), 2005)
Dutch government adopts an active policy to revitalize cities in general and to renew particular problematic housing areas in particular. In the majority of large cities the share of social housing is very large, mostly more than 50%. As a result we observe an increasing concentration of low-income households in the city and selective migration by middle and high income households from the city to the suburb. Official national housing and urban renewal policy is aiming at a redifferentiation of the urban housing stock: more owner-occupation, larger homes with a higher quality and a larger share of houses with a garden. This means: demolishing social housing estates, selling social housing or renovating social housing. The dominant actor in Dutch social housing is the housing association, which has a market share of 36% of the housing stock nationwide. Their position in the regeneration of Dutch urban districts is peculiar. They are supposed to take initiative and to invest in urban renewal and in the same time they are urged to reduce their market share. How are housing associations coping with this contradictory challenge? In this paper we will provide an overview of practices in Dutch cities and we will try to explain what we observe.
Keywords: 330